A low VOC S Adhesive tape and method for preparing the same
By introducing specific reactions, anti -aging monomers, and modified fillers in acrylic compression sensitivity, monomer convergence and suspended straight coating method is used to prepare an excellent adhesion, heat resistance and low VOCS characteristics The car wire beam tape solves the problem that the traditional tape is difficult to meet the requirements of low VOCs and high heat resistance.
Patent Information
- Application Number
- CN202410994278.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-24
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-07-24
AI Technical Summary
Traditional acrylic pressure-sensitive adhesives are difficult to meet the low VOCS and high heat resistance requirements of automotive wiring harness tape, and their monomer selection affects their high temperature resistance and adhesion.
By introducing specific components and proportional reaction monomers in acrylic compression, combined with anti -aging monomer and modified fillers, the monomer convergence method and suspended direct coating are prepared for low VOCs tape.
It improves the adhesion, internal aggregation, heat resistance and aging resistance of the tape, and meets the requirements of low VOCs and high heat resistance.
Smart Images

Figure BDA0004959703040000091 
Figure BDA0004959703040000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of acrylic pressure-sensitive adhesives, and in particular to a low VOC S Adhesive tape and method for preparing the same. Background Art
[0002] In recent years, with the continuous increase in sales of high-end cars, the country's low VOC S With the gradual implementation of the policy on volatile organic compounds (VOCs), the demand for environmentally friendly high-temperature resistant automotive wiring harness tapes has also increased significantly. Automotive wiring harness tapes generally include a substrate and an adhesive; they have high requirements for temperature resistance, insulation, and electromagnetic wave shielding. Among them, acrylic pressure-sensitive adhesives have good adhesion and weather resistance, and have gradually become an ideal choice for automotive wiring harness tapes; however, wiring harness tapes made with traditional acrylic pressure-sensitive adhesives are generally difficult to achieve low VOC. S requirements, and car manufacturers usually have requirements for interior odor and VOC S On the other hand, acrylic pressure-sensitive adhesive is obtained by copolymerization of reactive monomers, but the choice of monomers will affect its high temperature resistance and adhesion; and the problems of poor cohesion under high temperature conditions and easy thermal oxidation aging also limit its use.
[0003] In summary, a heat-resistant and low-VOC S Adhesive tape, which is suitable for automotive wiring harness tape, has important practical value. Summary of the invention
[0004] The object of the present invention is to provide a low VOC S The invention discloses an adhesive tape and a preparation method thereof to solve the problems raised in the above background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A low VOC S The method for preparing the adhesive tape comprises the following steps:
[0007] Step 1: adding the reaction monomer and the initiator to ethanol in sequence for copolymerization to obtain an adhesive;
[0008] Step 2: Apply the adhesive to the substrate surface and dry it at 60-110°C to obtain a low VOC S adhesive tape.
[0009] More optimally, the coating method is a suspension direct coating method.
[0010] More optimally, the reaction monomers include the following components: by weight, 80-90 parts of isooctyl acrylate, 4-8 parts of vinyl acetate, and 8-12 parts of methacrylic acid; the initiator accounts for 0.4wt% to 0.8wt% of the reaction monomers.
[0011] More optimally, the solid content of the adhesive is 45±1%; the viscosity of the adhesive is 60000mpa.s to 100000mpa.s.
[0012] Preferably, the copolymerization process adopts a stepwise addition method, which specifically includes the following steps:
[0013] Take a part of the reaction monomer and the first part of the initiator and add them to ethanol in sequence, control the temperature to 65-70°C and react for 1-1.5 hours; add the remaining reaction monomer and the second part of the initiator dropwise, and the dropping time is 100-110 minutes; control the temperature to 70-75°C and react for 7-8 hours. During the reaction, add the remaining third part of the initiator in batches every 1.5 hours; adjust the solid content to obtain an adhesive.
[0014] More optimally, the adhesive also includes an anti-aging monomer and a modified filler; the anti-aging monomer accounts for 2wt% to 3wt% of the reaction monomer; the modified filler accounts for 5wt% to 6wt% of the adhesive; the filler in the modified filler includes aluminum oxide and aluminum nitride in a mass ratio of 3:7.
[0015] More optimally, the anti-aging monomer and the modified filler both contain polyethylene glycol borate; the preparation method of the polyethylene glycol borate is: mixing polyethylene glycol and 4-pentenylboric acid in a molar ratio of 2 to 2.2:1, stirring and reacting at 120 to 130° C. for 3 to 4 hours to obtain polyethylene glycol borate.
[0016] Preferably, the average number n of oxyethylene groups in the polyethylene glycol is 4-5.
[0017] More optimally, the preparation method of the anti-aging monomer comprises the following steps: (1) adding 5-amino-2-pyridinecarboxylic acid to ethanol and stirring evenly, adding potassium hydroxide aqueous solution, dripping 3,5-di-tert-butyl-2-hydroxybenzaldehyde solution, setting the temperature to 58-62°C and reacting for 4-5 hours; cooling, setting the temperature to 0-5°C, dripping sodium borohydride solution, stirring for 2-3 hours, adjusting the pH to 5-5.5 with an acid solution, filtering, and drying to obtain an anti-aging agent; (2) adding the anti-aging agent and polyethylene glycol borate to dichlorothionyl in sequence and stirring evenly, adding a mixed solution containing EDC and NHS, stirring at 60-70°C for 48 hours, washing, and drying to obtain an anti-aging monomer.
[0018] More optimally, polyethylene glycol borate and methacryloxypropyltrimethoxysilane are added to a mixed solvent of deionized water and tert-butyl alcohol, and fillers are added, ground and mixed, freeze-dried, and ground to obtain modified fillers.
[0019] Optimally, a low VOCS Low VOC produced by the method for preparing adhesive tape S adhesive tape.
[0020] Compared with the prior art, the present invention has the following beneficial effects: a low VOC S Adhesive tape; by introducing reactive monomers of specific components and proportions therein; and further combining the introduction of anti-aging monomers and modified fillers to effectively improve its adhesion and cohesion; and improve its heat resistance and aging resistance.
[0021] Among them, isooctyl acrylate is used as the main reaction monomer; and is combined with vinyl acetate and methacrylic acid containing polar molecules; because most of it is isooctyl acrylate, which is a soft monomer with a longer alkyl chain, it has better cohesion and higher adhesion; however, due to its longer chain length, although the copolymer has more chain entanglement, the internal hydrogen bond effect is lower; therefore, the bonding performance still needs to be improved. Therefore, the scheme further introduces anti-aging monomers and modified fillers containing polyethylene glycol borate to further increase the bonding performance.
[0022] Among them, polyethylene glycol borate is obtained by reacting polyethylene glycol and 4-pentenylboronic acid to make it contain reactive olefin groups and polyethylene glycol segments; its introduction improves the high temperature resistance and flame retardancy of the adhesive, and another scheme has viscosity-enhancing properties due to the introduction of its oxygen-containing segments; it improves cohesion and adhesion at the same time; however, the average number of oxyethylene groups in its molecular segments needs to be limited; too large a number will affect the subsequent copolymerization of the adhesive, reduce the cross-linking network of the adhesive, and affect the overall performance of the acrylic pressure-sensitive adhesive.
[0023] Among them, the anti-aging monomer is an antioxidant anti-aging agent containing hindered phenols prepared by reacting the amino group in 5-amino-2-pyridinecarboxylic acid with the aldehyde group in 3,5-di-tert-butyl-2-hydroxybenzaldehyde; and the carboxyl group contained is cross-linked with the hydroxyl group in polyethylene glycol borate to obtain an anti-aging monomer; among them, since the grafted polyethylene glycol borate has macromolecularity and reactivity; therefore, compared with common anti-aging agents, the anti-aging monomer in this application has good migration resistance. On the other hand, due to the secondary amine groups it contains, it can effectively increase the hydrogen bonding effect in the adhesive, increase cohesion and adhesion; and the pyridine group and benzene ring contained can improve heat resistance and flame retardancy.
[0024] Among them, by modifying the filler with polyethylene glycol borate, the aggregation of the filler can be effectively inhibited and its dispersibility in the crosslinking agent can be increased. In the scheme, the addition of fillers can increase cohesion, provide peeling force, increase heat resistance and flame retardancy. At the same time, a specific proportion of aluminum oxide and aluminum nitride is introduced in the scheme, which has good thermal conductivity and electrical insulation. Compared with a single filler, the mixture of the two can reduce the amount of filler introduced while ensuring electrical insulation and heat resistance. Because higher fillers will affect its mechanical properties, it will cause the glue to break. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] It should be noted that the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions. Examples include: The glue coating amount in the following comparative examples and embodiments is 30 g / m 3 ; The base film is a PET base film; the specification of aluminum oxide is 60nm; purchased from Yumu Ningbo New Materials Co., Ltd.; the product number of aluminum nitride is WD0896, purchased from aluminum nitride; the other chemical raw materials involved are commercially purchased.
[0027] The following parts are all by mass.
[0028] Example 1: A low VOC S The method for preparing the adhesive tape comprises the following steps:
[0029] Raw material preparation: weigh 85 parts of isooctyl acrylate, 5 parts of vinyl acetate, and 10 parts of methacrylic acid as reaction monomers; weigh 0.5wt% of the reaction monomer mass of dimethyl azobisisobutyrate as initiator;
[0030] Step 1: Take 40wt% of the reaction monomer and 0.1wt% of dimethyl azobisisobutyrate and add them to ethanol in sequence, control the temperature to 60°C and react for 1 hour; add the remaining 60wt% of the reaction monomer and 0.25wt% of dimethyl azobisisobutyrate dropwise for 100 minutes; control the temperature to 70°C and react for 8 hours. During the reaction, add the remaining 0.15wt% of dimethyl azobisisobutyrate in batches every 1.5 hours; adjust the solid content to 45% to obtain an adhesive.
[0031] Step 2: Apply the adhesive to the substrate surface using the suspension direct coating method and dry it at 80°C to obtain a low VOC S adhesive tape.
[0032] Example 2: A low VOC S The method for preparing the adhesive tape comprises the following steps:
[0033] Raw material preparation: (1) polyethylene glycol-200 and 4-pentenylboronic acid were mixed in a molar ratio of 2.1:1, and stirred at 125° C. for 4 hours to obtain polyethylene glycol borate;
[0034] (2) weighing aluminum oxide and aluminum nitride in a mass ratio of 3:7 as fillers; adding 8 parts of polyethylene glycol borate and 2 parts of methacryloxypropyltrimethoxysilane to a mixed solvent of 80 parts of deionized water and 20 parts of tert-butyl alcohol, adding 15 parts of fillers, grinding and mixing at 100 rpm for 72 hours, freeze-drying, grinding, and obtaining a modified filler;
[0035] (3) adding 9.7 parts of 5-amino-2-pyridinecarboxylic acid to 150 parts of ethanol and stirring evenly, adding potassium hydroxide aqueous solution (4.5 parts of potassium hydroxide, 15 parts of deionized water), dropping 3,5-di-tert-butyl-2-hydroxybenzaldehyde solution (23 parts of 3,5-di-tert-butyl-2-hydroxybenzaldehyde, 100 parts of ethanol), setting the temperature to 60°C for reaction for 4 hours; cooling, setting the temperature to an ice bath, dropping sodium borohydride solution (3.6 parts of sodium borohydride, 50 parts of deionized water, 50 parts of ethanol), stirring for 2 hours, adjusting the pH to 5.2 with hydrochloric acid solution, filtering, and drying to obtain an anti-aging agent; adding 2 parts of the anti-aging agent and 10 parts of polyethylene glycol borate to 50 parts of dichlorothionyl in sequence and stirring evenly, adding a mixed solution containing 2 parts of EDC and 3 parts of NHS, stirring at 70°C for 48 hours, washing, and drying to obtain an anti-aging monomer;
[0036] (3) Weighing 85 parts of isooctyl acrylate, 5 parts of vinyl acetate, and 10 parts of methacrylic acid as reaction monomers; weighing 0.5 wt% of the reaction monomer mass of dimethyl azobisisobutyrate as an initiator; weighing 3 wt% of the reaction monomer mass of an anti-aging monomer; and weighing 5 wt% of the reaction monomer mass of a modified filler;
[0037] Step 1: Take 50wt% of the reaction monomer, the modified filler, and 0.1wt% of dimethyl azobisisobutyrate and add them to ethanol in sequence, control the temperature to 60°C and react for 1 hour; add the remaining 50wt% of the reaction monomer and 0.25wt% of dimethyl azobisisobutyrate dropwise for 100 minutes; add the anti-aging monomer; control the temperature to 70°C and react for 8 hours. During the reaction, add the remaining 0.15wt% of the initiator in batches every 1.5 hours; adjust the solid content to 45% to obtain an adhesive.
[0038] Step 2: Apply the adhesive to the substrate surface using the suspension direct coating method and dry it at 80°C to obtain a low VOC S adhesive tape.
[0039] Example 3: A low VOC S The method for preparing the adhesive tape comprises the following steps:
[0040] Raw material preparation: (1) polyethylene glycol-200 and 4-pentenylboronic acid were mixed in a molar ratio of 2.1:1, and stirred at 125° C. for 4 hours to obtain polyethylene glycol borate;
[0041] (2) weighing aluminum oxide and aluminum nitride in a mass ratio of 3:7 as fillers; adding 8 parts of polyethylene glycol borate and 2 parts of methacryloxypropyltrimethoxysilane to a mixed solvent of 80 parts of deionized water and 20 parts of tert-butyl alcohol, adding 15 parts of fillers, grinding and mixing at 100 rpm for 72 hours, freeze-drying, grinding, and obtaining a modified filler;
[0042] (3) adding 9.7 parts of 5-amino-2-pyridinecarboxylic acid to 150 parts of ethanol and stirring evenly, adding potassium hydroxide aqueous solution (4.5 parts of potassium hydroxide, 15 parts of deionized water), dropping 3,5-di-tert-butyl-2-hydroxybenzaldehyde solution (23 parts of 3,5-di-tert-butyl-2-hydroxybenzaldehyde, 100 parts of ethanol), setting the temperature to 60°C for reaction for 4 hours; cooling, setting the temperature to an ice bath, dropping sodium borohydride solution (3.6 parts of sodium borohydride, 50 parts of deionized water, 50 parts of ethanol), stirring for 2 hours, adjusting the pH to 5.2 with hydrochloric acid solution, filtering, and drying to obtain an anti-aging agent; adding 2 parts of the anti-aging agent and 10 parts of polyethylene glycol borate to 50 parts of dichlorothionyl in sequence and stirring evenly, adding a mixed solution containing 2 parts of EDC and 3 parts of NHS, stirring at 70°C for 48 hours, washing, and drying to obtain an anti-aging monomer;
[0043] (3) Weighing 80 parts of isooctyl acrylate, 8 parts of vinyl acetate, and 12 parts of methacrylic acid as reaction monomers; weighing 0.5 wt% of the reaction monomer mass of dimethyl azobisisobutyrate as an initiator; weighing 3 wt% of the reaction monomer mass of an anti-aging monomer; and weighing 5 wt% of the reaction monomer mass of a modified filler;
[0044] Step 1: Take 50wt% of the reaction monomer, the modified filler, and 0.1wt% of dimethyl azobisisobutyrate and add them to ethanol in sequence, control the temperature to 60°C and react for 1 hour; add the remaining 50wt% of the reaction monomer and 0.25wt% of dimethyl azobisisobutyrate dropwise for 100 minutes; add the anti-aging monomer; control the temperature to 70°C and react for 8 hours. During the reaction, add the remaining 0.15wt% of the initiator in batches every 1.5 hours; adjust the solid content to 45% to obtain an adhesive.
[0045] Step 2: Apply the adhesive to the substrate surface using the suspension direct coating method and dry it at 80°C to obtain a low VOC Sadhesive tape.
[0046] Example 4: A low VOC S The method for preparing the adhesive tape comprises the following steps:
[0047] Raw material preparation: (1) polyethylene glycol-200 and 4-pentenylboronic acid were mixed in a molar ratio of 2.1:1, and stirred at 125° C. for 4 hours to obtain polyethylene glycol borate;
[0048] (2) weighing aluminum oxide and aluminum nitride in a mass ratio of 3:7 as fillers; adding 8 parts of polyethylene glycol borate and 2 parts of methacryloxypropyltrimethoxysilane to a mixed solvent of 80 parts of deionized water and 20 parts of tert-butyl alcohol, adding 15 parts of fillers, grinding and mixing at 100 rpm for 72 hours, freeze-drying, grinding, and obtaining a modified filler;
[0049] (3) adding 9.7 parts of 5-amino-2-pyridinecarboxylic acid to 150 parts of ethanol and stirring evenly, adding potassium hydroxide aqueous solution (4.5 parts of potassium hydroxide, 15 parts of deionized water), dropping 3,5-di-tert-butyl-2-hydroxybenzaldehyde solution (23 parts of 3,5-di-tert-butyl-2-hydroxybenzaldehyde, 100 parts of ethanol), setting the temperature to 60°C for reaction for 4 hours; cooling, setting the temperature to an ice bath, dropping sodium borohydride solution (3.6 parts of sodium borohydride, 50 parts of deionized water, 50 parts of ethanol), stirring for 2 hours, adjusting the pH to 5.2 with hydrochloric acid solution, filtering, and drying to obtain an anti-aging agent; adding 2 parts of the anti-aging agent and 10 parts of polyethylene glycol borate to 50 parts of dichlorothionyl in sequence and stirring evenly, adding a mixed solution containing 2 parts of EDC and 3 parts of NHS, stirring at 70°C for 48 hours, washing, and drying to obtain an anti-aging monomer;
[0050] (3) Weighing 90 parts of isooctyl acrylate, 4 parts of vinyl acetate, and 8 parts of methacrylic acid as reaction monomers; weighing 0.5 wt% of the reaction monomer mass of dimethyl azobisisobutyrate as an initiator; weighing 2 wt% of the reaction monomer mass of an anti-aging monomer; and weighing 6 wt% of the reaction monomer mass of a modified filler;
[0051] Step 1: Take 50wt% of the reaction monomer, the modified filler, and 0.1wt% of dimethyl azobisisobutyrate and add them to ethanol in sequence, control the temperature to 60°C and react for 1 hour; add the remaining 50wt% of the reaction monomer and 0.25wt% of dimethyl azobisisobutyrate dropwise for 100 minutes; add the anti-aging monomer; control the temperature to 70°C and react for 8 hours. During the reaction, add the remaining 0.15wt% of the initiator in batches every 1.5 hours; adjust the solid content to 45% to obtain an adhesive.
[0052] Step 2: Apply the adhesive to the substrate surface using the suspension direct coating method and dry it at 80°C to obtain a low VOCS adhesive tape.
[0053] Comparative Example 1: Polyethylene glycol borate was not introduced, and the rest was the same as Example 2; the details are as follows:
[0054] Raw material preparation: (1) weighing aluminum oxide and aluminum nitride in a mass ratio of 3:7 as fillers; adding 10 parts of methacryloxypropyltrimethoxysilane to a mixed solvent of 80 parts of deionized water and 20 parts of tert-butyl alcohol, adding 15 parts of fillers, grinding and mixing at 100 rpm for 72 hours, freeze-drying, grinding, and obtaining a modified filler;
[0055] (3) Add 9.7 parts of 5-amino-2-pyridinecarboxylic acid to 150 parts of ethanol and stir evenly, add potassium hydroxide aqueous solution (4.5 parts of potassium hydroxide, 15 parts of deionized water), add 3,5-di-tert-butyl-2-hydroxybenzaldehyde solution (23 parts of 3,5-di-tert-butyl-2-hydroxybenzaldehyde, 100 parts of ethanol), set the temperature to 60°C and react for 4 hours; cool, set the temperature to an ice bath, add sodium borohydride solution (3.6 parts of sodium borohydride, 50 parts of deionized water, 50 parts of ethanol), stir for 2 hours, adjust the pH to 5.2 with hydrochloric acid solution, filter and dry to obtain an anti-aging agent; add 2 parts of anti-aging agent and 4 parts of hydroxyethyl acrylate to 50 parts of dichlorothionyl in sequence and stir evenly, add a mixed solution containing 1 part of EDC and 1.5 parts of NHS, stir at 70°C for 48 hours, wash and dry to obtain an anti-aging monomer;
[0056] (3) Weighing 85 parts of isooctyl acrylate, 5 parts of vinyl acetate, and 10 parts of methacrylic acid as reaction monomers; weighing 0.5 wt% of the reaction monomer mass of dimethyl azobisisobutyrate as an initiator; weighing 3 wt% of the reaction monomer mass of an anti-aging monomer; and weighing 5 wt% of the reaction monomer mass of a modified filler;
[0057] Step 1: Take 50wt% of the reaction monomer, the modified filler, and 0.1wt% of dimethyl azobisisobutyrate and add them to ethanol in sequence, control the temperature to 60°C and react for 1 hour; add the remaining 50wt% of the reaction monomer and 0.25wt% of dimethyl azobisisobutyrate dropwise for 100 minutes; add the anti-aging monomer; control the temperature to 70°C and react for 8 hours. During the reaction, add the remaining 0.15wt% of the initiator in batches every 1.5 hours; adjust the solid content to 45% to obtain an adhesive.
[0058] Step 2: Apply the adhesive to the substrate surface using the suspension direct coating method and dry it at 80°C to obtain a low VOC S adhesive tape.
[0059] Comparative Example 2: Polyethylene glycol-200 is replaced with polyethylene glycol-400, and the rest is the same as Example 2; the details are as follows:
[0060] Preparation of raw materials: (1) polyethylene glycol-400 and 4-pentenylboronic acid in a molar ratio of 2.1:1 were mixed, and stirred at 125° C. for 4 hours to obtain polyethylene glycol borate;
[0061] (2) weighing aluminum oxide and aluminum nitride in a mass ratio of 3:7 as fillers; adding 8 parts of polyethylene glycol borate and 2 parts of methacryloxypropyltrimethoxysilane to a mixed solvent of 80 parts of deionized water and 20 parts of tert-butyl alcohol, adding 15 parts of fillers, grinding and mixing at 100 rpm for 72 hours, freeze-drying, grinding, and obtaining a modified filler;
[0062] (3) adding 9.7 parts of 5-amino-2-pyridinecarboxylic acid to 150 parts of ethanol and stirring evenly, adding potassium hydroxide aqueous solution (4.5 parts of potassium hydroxide, 15 parts of deionized water), dropping 3,5-di-tert-butyl-2-hydroxybenzaldehyde solution (23 parts of 3,5-di-tert-butyl-2-hydroxybenzaldehyde, 100 parts of ethanol), setting the temperature to 60°C for reaction for 4 hours; cooling, setting the temperature to an ice bath, dropping sodium borohydride solution (3.6 parts of sodium borohydride, 50 parts of deionized water, 50 parts of ethanol), stirring for 2 hours, adjusting the pH to 5.2 with hydrochloric acid solution, filtering, and drying to obtain an anti-aging agent; adding 2 parts of the anti-aging agent and 10 parts of polyethylene glycol borate to 50 parts of dichlorothionyl in sequence and stirring evenly, adding a mixed solution containing 2 parts of EDC and 3 parts of NHS, stirring at 70°C for 48 hours, washing, and drying to obtain an anti-aging monomer;
[0063] (3) Weighing 85 parts of isooctyl acrylate, 5 parts of vinyl acetate, and 10 parts of methacrylic acid as reaction monomers; weighing 0.5 wt% of the reaction monomer mass of dimethyl azobisisobutyrate as an initiator; weighing 3 wt% of the reaction monomer mass of an anti-aging monomer; and weighing 5 wt% of the reaction monomer mass of a modified filler;
[0064] Step 1: Take 50wt% of the reaction monomer, the modified filler, and 0.1wt% of dimethyl azobisisobutyrate and add them to ethanol in sequence, control the temperature to 60°C and react for 1 hour; add the remaining 50wt% of the reaction monomer and 0.25wt% of dimethyl azobisisobutyrate dropwise for 100 minutes; add the anti-aging monomer; control the temperature to 70°C and react for 8 hours. During the reaction, add the remaining 0.15wt% of the initiator in batches every 1.5 hours; adjust the solid content to 45% to obtain an adhesive.
[0065] Step 2: Apply the adhesive to the substrate surface using the suspension direct coating method and dry it at 80°C to obtain a low VOC S adhesive tape.
[0066] Comparative Example 3: Alumina was introduced as a filler, and the rest was the same as Example 2; the details are as follows:
[0067] Raw material preparation: (1) polyethylene glycol-200 and 4-pentenylboronic acid were mixed in a molar ratio of 2.1:1, and stirred at 125° C. for 4 hours to obtain polyethylene glycol borate;
[0068] (2) weighing alumina as a filler; adding 8 parts of polyethylene glycol borate and 2 parts of methacryloxypropyltrimethoxysilane to a mixed solvent of 80 parts of deionized water and 20 parts of tert-butyl alcohol, adding 15 parts of the filler, grinding and mixing at 100 rpm for 72 hours, freeze-drying, and grinding to obtain a modified filler;
[0069] (3) adding 9.7 parts of 5-amino-2-pyridinecarboxylic acid to 150 parts of ethanol and stirring evenly, adding potassium hydroxide aqueous solution (4.5 parts of potassium hydroxide, 15 parts of deionized water), dropping 3,5-di-tert-butyl-2-hydroxybenzaldehyde solution (23 parts of 3,5-di-tert-butyl-2-hydroxybenzaldehyde, 100 parts of ethanol), setting the temperature to 60°C for reaction for 4 hours; cooling, setting the temperature to an ice bath, dropping sodium borohydride solution (3.6 parts of sodium borohydride, 50 parts of deionized water, 50 parts of ethanol), stirring for 2 hours, adjusting the pH to 5.2 with hydrochloric acid solution, filtering, and drying to obtain an anti-aging agent; adding 2 parts of the anti-aging agent and 10 parts of polyethylene glycol borate to 50 parts of dichlorothionyl in sequence and stirring evenly, adding a mixed solution containing 2 parts of EDC and 3 parts of NHS, stirring at 70°C for 48 hours, washing, and drying to obtain an anti-aging monomer;
[0070] (3) Weighing 85 parts of isooctyl acrylate, 5 parts of vinyl acetate, and 10 parts of methacrylic acid as reaction monomers; weighing 0.5 wt% of the reaction monomer mass of dimethyl azobisisobutyrate as an initiator; weighing 3 wt% of the reaction monomer mass of an anti-aging monomer; and weighing 5 wt% of the reaction monomer mass of a modified filler;
[0071] Step 1: Take 50wt% of the reaction monomer, the modified filler, and 0.1wt% of dimethyl azobisisobutyrate and add them to ethanol in sequence, control the temperature to 60°C and react for 1 hour; add the remaining 50wt% of the reaction monomer and 0.25wt% of dimethyl azobisisobutyrate dropwise for 100 minutes; add the anti-aging monomer; control the temperature to 70°C and react for 8 hours. During the reaction, add the remaining 0.15wt% of the initiator in batches every 1.5 hours; adjust the solid content to 45% to obtain an adhesive.
[0072] Step 2: Apply the adhesive to the substrate surface using the suspension direct coating method and dry it at 80°C to obtain a low VOC S adhesive tape.
[0073] Comparative Example 4: The amount of modified filler introduced was increased, and the rest was the same as Example 2; the details are as follows:
[0074] Preparation of raw materials: (1) polyethylene glycol-200 and 4-pentenylboronic acid in a molar ratio of 2.1:1 were mixed, and stirred at 125° C. for 4 hours to obtain polyethylene glycol borate;
[0075] (2) weighing aluminum oxide and aluminum nitride in a mass ratio of 3:7 as fillers; adding 8 parts of polyethylene glycol borate and 2 parts of methacryloxypropyltrimethoxysilane to a mixed solvent of 80 parts of deionized water and 20 parts of tert-butyl alcohol, adding 15 parts of fillers, grinding and mixing at 100 rpm for 72 hours, freeze-drying, grinding, and obtaining a modified filler;
[0076] (3) adding 9.7 parts of 5-amino-2-pyridinecarboxylic acid to 150 parts of ethanol and stirring evenly, adding potassium hydroxide aqueous solution (4.5 parts of potassium hydroxide, 15 parts of deionized water), dropping 3,5-di-tert-butyl-2-hydroxybenzaldehyde solution (23 parts of 3,5-di-tert-butyl-2-hydroxybenzaldehyde, 100 parts of ethanol), setting the temperature to 60°C for reaction for 4 hours; cooling, setting the temperature to an ice bath, dropping sodium borohydride solution (3.6 parts of sodium borohydride, 50 parts of deionized water, 50 parts of ethanol), stirring for 2 hours, adjusting the pH to 5.2 with hydrochloric acid solution, filtering, and drying to obtain an anti-aging agent; adding 2 parts of the anti-aging agent and 10 parts of polyethylene glycol borate to 50 parts of dichlorothionyl in sequence and stirring evenly, adding a mixed solution containing 2 parts of EDC and 3 parts of NHS, stirring at 70°C for 48 hours, washing, and drying to obtain an anti-aging monomer;
[0077] (3) Weighing 85 parts of isooctyl acrylate, 5 parts of vinyl acetate, and 10 parts of methacrylic acid as reaction monomers; weighing 0.5 wt% of the reaction monomer mass of dimethyl azobisisobutyrate as an initiator; weighing 3 wt% of the reaction monomer mass of an anti-aging monomer; and weighing 10 wt% of the reaction monomer mass of a modified filler;
[0078] Step 1: Take 50wt% of the reaction monomer, the modified filler, and 0.1wt% of dimethyl azobisisobutyrate and add them to ethanol in sequence, control the temperature to 60°C and react for 1 hour; add the remaining 50wt% of the reaction monomer and 0.25wt% of dimethyl azobisisobutyrate dropwise for 100 minutes; add the anti-aging monomer; control the temperature to 70°C and react for 8 hours. During the reaction, add the remaining 0.15wt% of the initiator in batches every 1.5 hours; adjust the solid content to 45% to obtain an adhesive.
[0079] Step 2: Apply the adhesive to the substrate surface using the suspension direct coating method and dry it at 80°C to obtain a low VOC S adhesive tape.
[0080] Performance test 1: The low VOC S The tape was tested for steel peeling performance; a universal material testing machine was used to test at room temperature and a peeling rate of 100 m / min, and the 180° peeling strength A was calculated; then it was placed at 150°C for 240 hours, and then tested again and the 180° peeling strength B was calculated; the obtained data are shown in the following table:
[0081]
[0082]
[0083] Results: From the data in the above table, it can be seen that this application has prepared a low VOC S Adhesive tape. The data of comparative examples 1 to 4 show that the introduction of polyethylene glycol borate segments can effectively improve the adhesion; and the length of the segments contained therein has an effect on the performance; at the same time, compared with a single filler, a specific proportion of composite fillers has better aging resistance; and further increase of fillers is not conducive to adhesion.
[0084] Performance Test 2: The low VOC S The tape was heated to 105°C for 180 minutes, and its mass before and after heating was measured with an accuracy of 0.001g; the non-volatile content was calculated;
[0085] Results: Non-volatile matter content 105μg / m 3 , with low VOC S sex.
[0086] Performance Test 3: The low VOC S The tape is subjected to support aging test and overload aging test.
[0087] Results: No glue overflow, cracking, relaxation or other aging after 3000 hours at 125°C; no glue overflow, cracking, relaxation or other aging after 6 hours at 200°C during overload aging, and no glue overflow, cracking, relaxation or other aging after 6 hours at -40°C. This shows that the low VOC S The tape has excellent bonding and heat resistance.
[0088] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A low VOC S The method for preparing the adhesive tape is characterized by: The following steps are involved: Step 1: adding the reaction monomer and the initiator to ethanol in sequence for copolymerization to obtain an adhesive; Step 2: Apply the adhesive to the substrate surface and dry it at 60~110℃ to obtain low VOC S adhesive tape; The reaction monomers include the following components: 80-90 parts of isooctyl acrylate, 4-8 parts of vinyl acetate, and 8-12 parts of methacrylic acid, by weight; the initiator accounts for 0.4wt%-0.8wt% of the reaction monomers; The adhesive further comprises an anti-aging monomer and a modified filler; the anti-aging monomer accounts for 2wt% to 3wt% of the reaction monomer; the modified filler accounts for 5wt% to 6wt% of the adhesive; the filler in the modified filler comprises aluminum oxide and aluminum nitride in a mass ratio of 3:7; the anti-aging monomer and the modified filler both contain polyethylene glycol borate; The preparation method of the anti-aging monomer comprises the following steps: (1) adding 5-amino-2-pyridinecarboxylic acid to ethanol and stirring evenly, adding potassium hydroxide aqueous solution, dropping 3,5-di-tert-butyl-2-hydroxybenzaldehyde solution, setting the temperature to 58-62°C for reaction for 4-5 hours; cooling, setting the temperature to 0-5°C, dropping sodium borohydride solution, stirring for 2-3 hours, adjusting the pH to 5-5.5 with an acid solution, filtering, drying, and obtaining an anti-aging agent; (2) adding the anti-aging agent and polyethylene glycol borate to dichlorothionyl in sequence and stirring evenly, adding a mixed solution containing EDC and NHS, stirring at 60-70°C for 48 hours, washing, and drying, and obtaining an anti-aging monomer; Polyethylene glycol borate and methacryloxypropyltrimethoxysilane are added to a mixed solvent of deionized water and tert-butyl alcohol, and fillers are added, ground and mixed, freeze-dried, and ground to obtain modified fillers.
2. A low VOC according to claim 1 S The method for preparing the adhesive tape is characterized by: The solid content of the adhesive is 45±1%; the viscosity of the adhesive is 60000mpa.s~100000mpa.s.
3. A low VOC according to claim 1 S The method for preparing the adhesive tape is characterized by: The copolymerization process adopts a step-by-step dropwise addition method, which specifically includes the following steps: Take a part of the reaction monomer and the first part of the initiator and add them to ethanol in sequence, control the temperature to 65-70°C and react for 1-1.5 hours; add the remaining reaction monomer and the second part of the initiator dropwise, and the addition time is 100-110 minutes; control the temperature to 70-75°C and react for 7-8 hours. During the reaction, add the remaining third part of the initiator in batches every 1.5 hours; adjust the solid content to obtain an adhesive.
4. A low VOC according to claim 1 S The method for preparing the adhesive tape is characterized by: The preparation method of the polyethylene glycol borate is as follows: polyethylene glycol and 4-pentenylboric acid are mixed at a molar ratio of 2-2.2:1, and stirred for reaction at 120-130° C. for 3-4 hours to obtain the polyethylene glycol borate.
5. A low VOC according to claim 1 S The method for preparing the adhesive tape is characterized by: The average number n of oxyethylene groups in the polyethylene glycol is 4-5.
6. A low VOC according to any one of claims 1 to 5 S Low VOC produced by the method for preparing adhesive tape S adhesive tape.
Citation Information
Patent Citations
Binder and preparation thereof
CN101475785A
Medical polyacrylate pressure-sensitive adhesive and its prodn. method
CN1110927A